Delivering mental health first aid training in Australian workplaces: exploring instructors' experiences. Issue 2 (14th March 2016) - Bovopoulos, Nataly; LaMontagne, Anthony; Martin, Angela; Jorm, Anthony
Abstract: The impact of common mental illnesses in the workplace can be reduced by encouraging support from co-workers and promoting early professional help-seeking. The Mental Health First Aid (MHFA) course is an evidence-based effective program designed to encourage social support and early help-seeking in the general community. However, little is known about whether the course meets the needs of workplaces. The current study aimed to gain a better understanding of how the course is being delivered in Australian workplaces and invite feedback on how it could be tailored for this delivery setting. This study used a purpose-designed survey to explore 120 MHFA instructors' experiences of delivering the course in workplaces. The results indicated that MHFA is most commonly deployed in the human service and education sectors to assist workers with helping clients, rather than helping co-workers. The results also suggest ways in which the MHFA course could be tailored for workplaces, as well as further support instructors require to deliver courses in workplace settings.